On input design for regularized LTI system identification: Power-constrained input. (November 2018) - Mu, Biqiang; Chen, Tianshi
Abstract: Input design is an important issue for classical system identification methods but has not been investigated for the kernel-based regularization method (KRM) until very recently. In this paper, we consider the input design problem of KRMs for LTI system identification. Different from the recent result, we adopt a Bayesian perspective and in particular make use of scalar measures (e.g., the A -optimality, D -optimality, and E -optimality) of the Bayesian mean square error matrix as the design criteria subject to power-constraint on the input. Instead of solving the optimization problem directly, we propose a two-step procedure. In the first step, by making suitable assumptions on the unknown input, we construct a quadratic map (transformation) of the input such that the transformed input design problems are convex, and the global minima of the transformed input design problem can thus be found efficiently by applying well-developed convex optimization software packages. In the second step, we derive the characterization of the optimal input based on the global minima found in the first step by solving the inverse image of the quadratic map. In addition, we derive analytic results for some special types of kernels, which provide insights on the input design and also its dependence on the kernel structure.